Intelligent chatbots in human resource management: development, architecture, and applications - Shmatko, O. V.; Bunin, M.; Шматко, О. В. (International Scientific Unity, 2025)
Artificial intelligence (AI) has become a crucial component in modern HRM systems, improving decision-making and employee satisfaction. AIdriven chatbots are designed to automate HR functions, facilitate employee interactions, and enhance recruitment processes. These virtual assistants simulate human communication, enabling organizations to optimize HR workflows efficiently. The integration of AI in HR systems is particularly relevant in the context of Industry 4.0, where automation and data-driven decision-making play a crucial role in business transformation.